Role of Inferior Vena Cava Parameters as Predictors of Fluid Responsiveness in Pediatric Septic Shock: A Prospective Study - EL-Nawawy, Ahmed Ahmed; Omar, Omneya Magdy; Hassouna, Hadir Mohamed (Journal of Child Science, 2021)
Fluid resuscitation is the initial therapy for septic shock worldwide. Prediction of fluid responsiveness is essential for optimizing fluid administration. Only few pediatric studies have evaluated the role of inferior vena cava (IVC) as a reliable predictor of fluid responsiveness. The aim of this study was to evaluate the role of IVC parameters as predictors of fluid responsiveness in children (under the age of 5 years) having septic shock at different times from admission. A prospective observational study included 51 children having septic shock. It was conducted in the nine-bedded pediatric intensive care unit of a university hospital from January 1, 2018, to the August 31, 2018. Echocardiography was used to assess minimal and maximal IVC diameters and its distensibility index with simultaneous assessment of stroke volume (SV), at 1, 6, and 24 hours from admission. The decision to give fluid in these children was thereby based on the presence of at least one sign of inadequate tissue perfusion. SV was reassessed directly after administration of a fluid bolus of 10 mL/kg over 10 minutes. Fluid responsiveness was considered adequate when there was ≥ 10% increase in SV after fluid bolus. Minimal IVC diameter indexed to body surface area and its distensibility index can be predictors of fluid responsiveness at all times: 1 hour (area under curve [AUC] = 0.88; 95% confidence interval [CI] = 0.77–0.96), 6 hours (AUC = 0.86; 95% CI = 0.67–0.97), and 24 hours (AUC = 0.77; 95% CI = 0.6–0.95). IVC distensibility index can also predict fluid responsiveness at 1 hour (AUC= 0.87; 95% CI = 0.74–0.95), 6 hours (AUC = 0.86; 95% CI = 0.73–0.94), and 24 hours (AUC = 1; 95% CI = 0.77–1). The cutoff points of each parameter differed from time to time (contradicts with previous statement that says it is predictor at all times). The maximum IVC diameter could not predict fluid responsiveness at any time from admission. Minimal IVC diameter and its distensibility index were feasible noninvasive surrogates of fluid responsiveness in pediatric septic shock at different times from admission.
Keywords: distensibility index; echocardiography; fluid responsiveness; inferior vena cava; pediatric septic shock